Bi‐Induced Few‐Layered Graphite Frameworks as Efficient Interfacial Transitions Toward Ultrafast Potassium Storage - Bozhi Yang; Xin Min; Xinyu Zhu; Shaorou Ke; Shujie Yang; Ya Chen; Wei Wang; Ruiyu Mi; Yangai Liu; Zhaohui Huang; Xi Kai; Minghao Fang; et al. (Advanced Science, 2025)
Abstract Bismuth is a promising anode material for potassium‐ion batteries due to its green, non‐toxic and high theoretical capacity (384 mAh g−1). However, the sluggish reaction kinetics and excessive volume expansion during cycling limit its practical application. Herein, Bi‐induced few‐layered graphite frameworks are in situ encapsulated on the surface of Bi nanoparticles, based on the mechanism of graphitization by rearrangement of interstitial carbon atoms during the nucleation process of Bi, while these composite particles are embedded in Bi‐doped porous carbon fibers composite. The graphite frameworks can stabilize the structure while serving as an efficient interfacial transfer layer, enabling rapid transport of both potassium ions and electrons. Bi atoms doped into the carbon fiber matrix effectively enhances the potassium ion transport kinetics in amorphous carbon by lowering the migration energy barrier of potassium ions in the carbon layer. The porous structure effectively alleviates the volume expansion of Bi nanoparticles during cycling, which synergistically results in superior high‐rate performance and cycling stability. Finally, the capacity can reach 215 mAh g−1 at 10 A g−1, and a capacity retention rate of 83.8% is achieved after 6000 cycles at 10 A g−1 with an ultra‐low decay rate of 0.00278% per cycle.